2017
DOI: 10.1111/tpj.13720
|View full text |Cite
|
Sign up to set email alerts
|

3D analysis of mitosis distribution highlights the longitudinal zonation and diarch symmetry in proliferation activity of the Arabidopsis thaliana root meristem

Abstract: To date CYCB1;1 marker and cortex cell lengths have been conventionally used to determine the proliferation activity of the Arabidopsis root meristem. By creating a 3D map of mitosis distribution we showed that these markers overlooked that stele and endodermis save their potency to divide longer than the cortex and epidermis. Cessation of cell divisions is not a random process, so that mitotic activity within the endodermis and stele shows a diarch pattern. Mitotic activity of all root tissues peaked at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…However, these conclusions were drawn based on labelled mitosis curves and did not consider the exponential age distribution of cells within the RAM (Ivanov, 1974(Ivanov, , 1994Webster and Davidson, 1980). Our analysis showed that the proximal portion of the RAM represents a transition domain where cells still divide (Lavrekha et al, 2017), and the relative cell growth rate is the same as in the rest of the RAM (Ivanov and Dubrovsky, 2013). Also, the duration of the last cell cycle in the RAM is the same as in the proliferation domain (Balodis and Ivanov, 1970), but exit from the cell cycle at the end of the RAM is a heterogeneous process.…”
Section: Discussionmentioning
confidence: 75%
“…However, these conclusions were drawn based on labelled mitosis curves and did not consider the exponential age distribution of cells within the RAM (Ivanov, 1974(Ivanov, , 1994Webster and Davidson, 1980). Our analysis showed that the proximal portion of the RAM represents a transition domain where cells still divide (Lavrekha et al, 2017), and the relative cell growth rate is the same as in the rest of the RAM (Ivanov and Dubrovsky, 2013). Also, the duration of the last cell cycle in the RAM is the same as in the proliferation domain (Balodis and Ivanov, 1970), but exit from the cell cycle at the end of the RAM is a heterogeneous process.…”
Section: Discussionmentioning
confidence: 75%
“…The formation of new LRs is a multistep process confined to the competent sector of the pericycle [54][55][56]. These cells exhibit a specific and prolonged cell cycling pattern [55,57,58] retaining their meristematic character (cell size, vacuolization, large nuclei and dense cytoplasm, G2 phase, cell division) longer than other root tissues [55,59,60]. ABERRANT LATERAL ROOT FORMATION 4 (ALF4) [61] is modulator of lateral root initiation maintaining the pericycle in a mitotically competent state [62].…”
Section: Lr Initiation and Developmentmentioning
confidence: 99%
“…Complex analyses of cell division and elongation patterns during primary root growth and development were mostly performed in model plants such as Arabidopsis (e.g., Beemster and Baskin, 1998 ; Beemster et al, 2002 ; Lavrekha et al, 2017 ), maize (e.g., Sacks et al, 1997 ), barley (e.g., Kirschner et al, 2017 ), tobacco (e.g., Pasternak et al, 2017 ) and rice (e.g., Rebouillat et al, 2009 ; Ni et al, 2014 ). These studies were mostly based on 3D reconstruction analyses from fixed plant samples.…”
Section: Introductionmentioning
confidence: 99%